ANALYSIS OF THE RELIABILITY OF THE LEE CLASSIFICATION FOR LUMBAR DISC HERNIATIONS - GONÇALVES,LUAN CELSO (2020)
ABSTRACT Objective To evaluate the intra- and interobserver reliability of the Lee et al. classification for migrated lumbar disc herniations. Methods In 2018, Ahn Y. et al. demonstrated the accuracy of this classification for radiologists. However, magnetic resonance images are often interpreted by orthopedists. Thus, a cross-sectional study was conducted by evaluating the magnetic resonance images of 82 patients diagnosed with lumbar disc herniation. The images were evaluated by 4 physicians, 3 of whom were spinal orthopedic specialists and 1 of whom was a radiologist. The intra- and interobserver analysis was conducted using the percentage of concordance and the Kappa method. Results The report of the classifications used by the four observers had a higher proportion of “zone 3” and “zone 4” type classifications in both evaluation moments. The most affected anatomical levels were L5-S1 (48.2%) and L4-L5 (41.4%). The intra- and interobserver concordance, when comparing both moments evaluation of the complementary examinations of the participants involved, was classified as moderate and very good. Conclusions Lee’s classification presented moderate to very good intra- and interobserver reliability for the evaluation of migrated lumbar disc herniation. Level of evidence II; Retrospective Study.